Orientation of head lice on human hosts, and consequences for transmission of pediculosis: the head lice movement studies - Heukelbach, Jorg (2017)
We performed head lice movement studies to elucidate factors influencing orientation and movement of head lice. Studies included observation of lice movements on hand and forearm at different positions of the upper limb; movements exposed to unshaved and shaved forearm; and movements with and without antennae. In 57 of 60 (95.0%) observations while holding the hand down, lice moved proximal, and 3 (5%) distal. While holding the hand up, 37/60 (61.7%) moved proximal, and 23 (38.3%) distal (p < 0.0001). On the unshaved limb, 29/30 (96.7%) moved proximal, with clockwise movements in 26/30 (86.7%). After shaving, 9/30 (30%) walked proximal and 18 (60%) distal, with 12/30 (40%) clockwise movements. After antennectomy, while holding the hand up, 16/25 (64%) lice did not move, 1 (4%) walked proximal, and 8 (32%) distal. While handing the hand down, 17/25 (68%) did not move, 5 (20%) walked proximal, and 3 (12%) distal. Transmission of head lice may not only occur by head-to-head contact, but also via head-to-body contact, with movement to the head against gravitational pull. Surface factors of hand and forearm may be important in orientation for lice, in addition to gravity. Movement of lice against gravity is not governed by organs in the antennae